Antiracist discourse: theory and history of a macromovement - Dijk, Teun A. van (Cambridge University Press, 2021)
Antiracism is a global and historical social movement of resistance and solidarity, yet there have been relatively few books focusing on it as a subject in its own right. After his earlier books on racist discourse, Teun A. van Dijk provides a theory of antiracism along with a history of discourse against slavery, racism and antisemitism. He first develops a multidisciplinary theory of antiracism, highlighting especially the role of discourse and cognition as forms of resistance and solidarity. He then covers the history of antiracist discourse, including antislavery and abolition discourse between the 16th and 19th century, antiracist discourse by white and black authors until the Civil Rights Movement and Black Lives Matter, and Jewish critical analysis of antisemitic ideas and discourse since the early 19th century. It is essential reading for anyone interested in how racism and antisemitism have been critically analysed and resisted in antislavery and antiracist discourse